The role assigned to health education in the Spain of the Democratic Transition - Perdiguero-Gil, Enrique (Historia y Memoria de la Educación, 2021)
In the mid-1970s, several health reform projects were discussed in Spain for the purpose of changing the outdated health system inherited from Francoism. In all these proposals, but especially in those promoted by the left¬ist parties, a primary role was assigned to the health education of the general population. In a health system that sought to defend health rather than cure diseases, the behaviour of the population in relation to the social and eco¬nomic factors that generated diseases was crucial. Furthermore, health edu¬cation was conceived as a way for the population to participate in the plan¬ning, management, and evaluation of health services. These generic statements were, on many occasions, naive and classic versions of health education, similar to those proposed by the government. The role of health education in rationalizing the use of health services was frequently invoked. Health re¬form projects tended to establish the hegemony of health workers over teach¬ers. Some more specific proposals gave way to more concrete actions at a local level that led to the development of the model of health education that was carried out in the following decades.